Fume emission during the arc and laser welding of cast stainless austenitic steel - J. Matusiak; J. Wycislik- Sosnierz (Metalurgija, 2023)
The article presents results of research on fume emission in relation to various arc welding methods (MAG standard, CMT, ColdArc and ColdArc Puls) and laser welding techniques (heat conduction and deep penetration welding). Research - related tests involved manifold elements and a turbine housing made of cast stainless steel. The shielding gas used during arc welding was a mixture containing 97,5 % of Ar and 2,5 % of CO2. In turn, laser welding processes were shielded by argon. The analysis of test results aimed to identify the effect of arc/laser welding methods on the total emission of welding fume.